2015
DOI: 10.1039/c5ta05242d
|View full text |Cite
|
Sign up to set email alerts
|

A novel mixture of diethylene glycol diethylether and non-flammable methyl-nonafluorobutyl ether as a safe electrolyte for lithium ion batteries

Abstract: A mixture of diethylene glycol diethylether and non-flammable methyl-nonafluorobutyl ether was introduced as a new electrolyte for lithium ion batteries. And a fluoroethylene carbonate additive was used in this electrolyte to improve the compatibility with the graphite anode. The non-flammability and high flash point of this electrolyte indicated its high safety. This electrolyte had low viscosity and its conductivity reached 3.8 mS cm À1 at 25 C. Graphite/LiFePO 4 coin cells with commercial electrodes were ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…An appropriate organic solvent is critically important not only for the dissolution of lithium orthoborate salt but also for oxidative stability, thermally stability, satisfactory conductivity, cell performance and life cycle 28 .Ether based organic solvents (also known as glymes) are gaining attentions in lithium ion batteries due to a number of advantages such as low viscosity, high thermal stability and safety 29 , 30 . Recently, a number of studies have demonstrated that mixtures of ionic liquids and glymes possess excellent electrolyte properties and are promising solvents for lithium-ion batteries 31 35 .…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate organic solvent is critically important not only for the dissolution of lithium orthoborate salt but also for oxidative stability, thermally stability, satisfactory conductivity, cell performance and life cycle 28 .Ether based organic solvents (also known as glymes) are gaining attentions in lithium ion batteries due to a number of advantages such as low viscosity, high thermal stability and safety 29 , 30 . Recently, a number of studies have demonstrated that mixtures of ionic liquids and glymes possess excellent electrolyte properties and are promising solvents for lithium-ion batteries 31 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Later, Fang et al developed a non-flammable electrolyte containing the aforementioned MFE as a co-solvent. 43 In their work LiFePO 4 //graphite full cells with 0.8 M LiTFSI in diethylene glycol diethyl ether (G2E), MFE and FEC (50 : 45 : 5 wt%) showed promising electrochemical performance close to cells with conventional electrolytes (1.0 M LiPF 6 -EC : DMC : DEC) at room temperature, but even at elevated and low temperatures. The capacity retention at À20 1C was about 46% after 200 cycles (62 mA h g À1 ).…”
Section: Non-flammable Co-solventsmentioning
confidence: 98%
“…[ 21 ] Consequently, it is very important to develop safe, nonflammable liquid electrolytes with comparable ionic conductivity and interfacial resistance as obtained for the current organic carbonate electrolytes. As reported in the literature, fluoroethers, [ 22 ] fluorophosphite, [ 23 ] and organosilicon compounds [ 24 ] have been investigated as nonflammable solvents for LIBs. Moreover, the low‐molecular‐weight phosphate‐based solvents with high solubility of Li and Na salts are particularly promising as they could enable an ionic conductivity comparable to that of carbonate‐based electrolytes.…”
Section: Introductionmentioning
confidence: 99%